Cold-water immersion after training sessions: effects on fiber type-specific adaptations in muscle K+ transport proteins to sprint-interval training in men - Christiansen, D.; Bishop, D. J.; Broatch, J. R.; Bangsbo, J.; McKenna, M. J.; Murphy, R. M. (Journal of Applied Physiology, 2018)
Effects of regular use of cold-water immersion (CWI) on fiber type-specific adaptations in muscle K+ transport proteins to intense training, along with their relationship to changes in mRNA levels after the first training session, were investigated in humans. Nineteen recreationally active men (24±6 yr, 79.5±10.8 kg, 44.6±5.8 ml·kg-1·min-1) completed six weeks of sprint-interval cycling, either without (passive rest; CON) or with training sessions followed by CWI (15 min at 10°C; COLD). Muscle biopsies were obtained before and after training to determine abundance of Na+, K+-ATPase isoforms (alpha 1-3, beta 1-3) and phospholemman (FXYD1) and after recovery treatments (+0 h and +3 h) on the first day of training to measure mRNA content. Training increased (P < 0.05) the abundance of alpha 1 and beta 3 in both fiber types and beta 1 in type-II fibers and decreased FXYD1 in type-I fibers, whereas alpha 2 and beta 3 abundance was not altered by training (P > 0.05). CWI after each session did not influence responses to training (P > 0.05). However, alpha 2 mRNA increased after the first session in COLD (+0 h, P < 0.05) but not in CON (P > 0.05). In both conditions, alpha 1 and beta 3 mRNA increased (+3 h; P < 0.05) and beta 2 mRNA decreased (+3 h; P < 0.05), whereas alpha 3, beta 1, and FXYD1 mRNA remained unchanged (P > 0.05) after the first session. In summary, Na+,K+-ATPase isoforms are differently regulated in type I and II muscle fibers by sprint-interval training in humans, which, for most isoforms, do not associate with changes in mRNA levels after the first training session. CWI neither impairs nor improves protein adaptations to intense training of importance for muscle K+ regulation. NEW & NOTEWORTHY Although cold-water immersion (CWI) after training and competition has become a routine for many athletes, limited published evidence exists regarding its impact on training adaptation. Here, we show that CWI can be performed regularly without impairing training-induced adaptations at the fiber-type level important for muscle K+ handling. Furthermore, sprint-interval training invoked fiber type-specific adaptations in K+ transport proteins, which may explain the dissociated responses of whole-muscle protein levels and K+ transport function to training previously reported.